Thyme: A natural preservative for seafood - Saman Yousefi (Infectious Diseases and Herbal Medicine, 2022)
Nowadays, food preservation for a long time without any change in quality is a global issue. Currently, 25 categories of food additives have been defined. These compounds are used to extend the shelf life of foods by protecting them against microorganisms as well as chemical reactions. Medicinal plants, having proven antimicrobial and antioxidant properties are suitable candidates for this purpose. Among them, thyme with a wide range of bioactive compounds has been extensively studied. This plant belongs to the family Lamiaceae and has a particular situation in traditional medicine. Nowadays, thyme and its derivate present a wide range of functional possibilities in the pharmacy and food industry. This article discusses thyme’s application as a food preservative in the seafood industry.